Highly Conductive and Fatigue‐Free Flexible Copper Film Electrode Fabricated by a Facile Dry Transfer Technique. Issue 1 (11th December 2017) - Shen, Shengfei; Zhu, Wei; Peng, Yuncheng; Hai, Fengxun; Feng, Jingjing; Deng, Yuan
Abstract: The flexible electrodes with excellent electrical and mechanical performance play critical and fundamental roles in the wearable electronics. In this work, highly conductive and fatigue‐free flexible copper thin‐film electrodes on polyethylene terephthalate substrate are successfully fabricated by a facile, nondestructive, and heat‐resistant dry transfer technique. Before the transfer process, the interface adhesive strength and electrical resistivity of Cu films on SiO2 +Si substrates are weakened and optimized. The flexible copper film electrode exhibits extremely low electrical resistivity (ρ = 3.1 µΩ cm), which is much superior to the flexible film electrodes fabricated through using the paste agent. Additionally, the fatigue experimental results show that the film electrode possesses excellent flexibility with a bending radius of 10 mm over 500 cycles due to the formation of the special microwavy structure, and is competent for a service environment with alternating temperature (−40–110 °C). It presents that the outstanding performance of flexible Cu film electrode is competent for most wearable electronics. The preparation of the advanced film electrode accelerates progress of the flexible electronics. Abstract : Highly conductive and fatigue‐free flexible copper thin‐film electrode on polyethylene terephthalate substrate is fabricated through a facile and nondestructive dry transfer technique. The whole process is solution free, scatheless, and effective. A feasible strategy to prepare the high‐performance flexible metal film electrode is provided in this work, which effectively promotes the development of the flexible electrons.